Impact of SARS-COV2 pandemic on emergency surgical services at Groote Schuur Hospital - Dookhony, Koshlen (Division of General Surgery, 2025)
Background: An international survey (98 collaborators from 31 countries) on the impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic on emergency surgery services revealed an 87.8% decrease in procedures. The aim of the study was to determine the impact of the coronavirus 19 (COVID-19) pandemic on the number of emergency surgical operations performed at Groote Schuur Hospital, Cape Town, South Africa. Methodology: The study was a retrospective cross-sectional study, comparing the number of emergency surgical operations performed before the COVID-19 pandemic to those performed during the COVID-19 lockdowns at Groote Schuur Hospital in Cape Town, South Africa. the data was retrieved from the Web Surgibank and Clinicom databases. Results: The total number of surgeries performed during the study period (April 2019 – March 2021) was 13715. The most frequently performed surgeries were orthopaedics (18.6%), hands (16.3%), acute surgery (16.5%), neurosurgery (10.5%) and trauma (10.1%). There were statistically significant differences in the number of surgeries before COVID-19 and during COVID-19 (p=.002). There was a 19.5% reduction in the number of surgeries. The mean number of surgeries during the pandemic was less compared to the pre COVID-19 period (p<.001). The patterns in the types of surgeries performed were similar before and during the various levels of the pandemic. There was a statistically significant difference in the number of surgeries performed across the various stages of the alcohol lockdowns. The increases and decreases varied across different conditions. From the first full alcohol ban (March to May 2020) to the first and 2nd alcohol partial ban (June to July 2020) – the numbers of emergency surgeries in thirteen out of the seventeen types of conditions continued to decrease while they increased in three conditions. The types of conditions that increased between the complete and partial alcohol ban were trauma (increased by 70.4%), ENT (increased by 41.1%), eyes (increased by 68.5%) and hands (increased by 3.4%). Conclusion: COVID-19 has significantly impacted the number of surgeries performed during the pandemic at Groote Schuur Hospital. In addition, alcohol ban has also significantly impacted the pattern of surgeries performed in our institution. This overall reduction was less compared to international centres. The lesser reduction is likely due to high incidence of trauma in South Africa as well as local hospital policy to maintain a contingency plan to avoid total collapse of the surgical system.